Moral Transformation as Shifting (Im)Possibilities - Caprioglio Panizza, Silvia; Vaccarezza, Maria Silvia (Springer Nature Switzerland AG, 2024)
The phenomenon of moral transformation, though important, has received little attention in virtue ethics. In this paper we propose a virtue-ethical model of moral transformation as character transformation by tracking the development of new identity-defining ('core') character traits, their expressions, and their priority structure, through the change in what appears as possible or impossible to the moral agent. We propose that character transformation culminates when what previously appeared as morally possible to the agent now appears impossible, i.e. unconceived and unthinkable, moving through stages of transformation where some possibilities gradually disappear while others open up. While we show an example of moral transformation towards virtue, we allow that such transformation can occur in the opposite direction, hence we make claims about 'character traits' rather than virtues of vices. Through the example of former slave-trader Rodrigo's transformation in the film The Mission, we follow the parallel development of new objects of value and ways of valuing (with respect to a group of indigenous people of South America) with the closing down of the possibility of disrespecting and harming them, to the end-point of transformation, where allowing their capture is for Rodrigo both unconceived and, when conceived, unthinkable.
Morální transformace jako posun (ne)možnosti
Keywords: Moral transformation; Character; Virtue ethics; Moral impossibility; Silencing; Unthinkability